The interplay between inter-personal and inter-organizational relationships in coordinating supply chain activities. Issue 3 (12th April 2021) - Saikouk, Tarik; Fattam, Nejib; Angappa, Gunasekaran; Hamdi, Ahmed
Abstract : Purpose: This paper aims to identify and explain the link between relational dynamics and the development of coordination capabilities of Fourth-Party Logistics Providers (4PL) within a supply chain (SC). We aim to demonstrate the critical role relational dynamics can play in converting trust from interpersonal to inter-organizational level and facilitate the improvement of capabilities to coordinate customer's SC activities. Design/methodology/approach: Using semi-structured interviews with 78 logistics managers operating in 45 different logistics service providers located in France, we developed a set of propositions and built a conceptual framework. Exploratory qualitative research in the form of propositional discourse analysis (PDA) is used to develop propositions in our research to contribute to theory in supply chain management (SCM). Findings: Results indicate that both interpersonal and inter-organizational trust is a convertible capital. Based on their dynamic interactions, these two levels of trust endow the supply chain partners with economic benefits that would otherwise be highly costly or even practically extremely difficult to achieve through complex socio-economic transactions (meso-social level). Research limitations/implications: Future research may test our conceptual model using primary and secondary data and conduct longitudinal case studies that are necessary to triangulate our results and thus strengthen our conclusions. The prospect of adding control variables to our model would be of considerable importance. Practical implications: Our results suggest that "4PL" need to invest more in interpersonal relations to facilitate collaboration with their clients and enhance their capability to coordinate and manage customer's supply chain activities. The ability to convert interpersonal trust represents an invaluable capital contributing to the achievement of above-normal profits. Originality/value: This work contributes to a better understanding of the coordination of supply chain activities through the development, mobilization and maintenance of social capital. While previous research explained the importance of trust in SCM, this paper explores and studies the process of converting interpersonal trust into social capital mobilized at the supply chain level. We add to the existing literature on structural and relational dimensions of social capital by offering a process-based explanation of the conversion of interpersonal trust into inter-organizational trust and its role in facilitating collaboration in logistics services.